THE ABILITY OF SPEAKING SKILL OF COMPUTER STUDENTS BY PRESENTING INFORMATION BASIC COMPUTER - Ulfa, Kurnia (Universitas Methodist Indonesia, 2023)
The goals of this study are to find out what is the good strategy to stimulate the students’ of computer engineering to study English easily and more active in practicing, besides that the lecturer can be more creative to stimulate and motivate the students’ especially the new students’ to have good impression of study and learning English in the class. This research was taken from the new students of 2022 in the first semester which “Presenting Information Basic Computer in English” by using video as speaking practice in English class. The participants of this research are fifty (50) students from the classroom lecturers which have been attended to get the top ten highest score video presentation. From the data can be shown that class TI-P2101 has got more than one student in highest score. The research to found what are the positive effects from this stimulate to the students that can be improve, and the negative effects to solve their problem and what the lecturer strategy is needed. By this video presentation students can be attract to learn English joyful without stress, and they can learn perfect English from their mistake in video presentation.